Problematode: an enigmatic new genus of Membracidae (Hemiptera) with two new species from Venezuela - Gaiani, Marco A. (Zootaxa, 2017)
The new Neotropical genus Problematode gen. nov. is described and illustrated to accommodate two new closely related species from the Coastal Montane Forests of Venezuela, P. sakakibarai sp. nov. and P. inerme sp. nov. Problematode gen. nov. appears to be closely related to Euwalkeria Goding on the basis of the reticulate venation of the forewing and lack of posterior pronotal processes, and to Smergotomia Dietrich and Smerdalea Fowler in the configuration of the anal veins of the forewing. The widely separated mid- and hind coxae, exposing the thoracic ventral sternites, and the fused mesothoracic trochanter and femur are unique features of these taxa, which are considered of uncertain position within Membracidae.